Comparative Perspectives on International School Leadership: Policy, Preparation, and Practice - Magno, Cathryn S. (Routledge, 2013)
Through a multi-country study, Comparative Perspectives on International School Leadership examines the current global spread of educational leadership, occurring rapidly and widely. Exploring five international case studies of leadership policy, preparation, and practice under the framework of policy borrowing and adaptation, Magno attempts to understand and account for commonalities and differences across country contexts. Rather than assuming a particular model or theory to leadership is best, Comparative Perspectives on International School Leadership takes a policy-orient
Keywords: Cross-cultural studies; Cross-cultural studies; School management and organization; Educational leadership; dept.edl; faculty_collection

The balanced curriculum model: Description and results - Squires, David (SAGE Open, 2013)
The Balanced Curriculum is a web-based tool that school districts use to create, align, assess, and manage their curriculum development and implementation. The courses are divided into time-bound units with significant tasks (or assured activities) that local district teachers develop and promise to teach. The significant tasks are aligned to standards and assessment specifications. District curriculum authors also develop assessments for all to use when implementing the curriculum. Results of more than 15 years of implementation show that all districts that have developed curriculum using this model, and ensured implementation, have had significant improvement on their test scores. Implications for teachers, principals, and central office staff are given at the end of the article. © The Author(s) 2013.
Keywords: Curriculum; Student achievement results; dept.edl